2003
DOI: 10.1212/01.wnl.0000069922.32557.ca
|View full text |Cite|
|
Sign up to set email alerts
|

Occurrence of amyotrophic lateral sclerosis among Gulf War veterans

Abstract: Military personnel who were deployed to the Gulf Region during the Gulf War period experienced a greater post-war risk of ALS than those who were not deployed to the Gulf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
183
4
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(193 citation statements)
references
References 27 publications
5
183
4
1
Order By: Relevance
“…One defined environmental risk is related to occupations, such as military veterans, varsity athletes, and professional football players. [65][66][67] Because these populations share the same risk which distinguished them from other populations, that is, they have increased chance of motor nerve injury, we reasoned that motor nerve injury might trigger the development and/or accelerate the progression of ALS. Therefore, we conducted a study to determine the immune responses after nerve injury in mouse ALS model.…”
Section: Th17 Cells Nerve Injury and Alsmentioning
confidence: 99%
“…One defined environmental risk is related to occupations, such as military veterans, varsity athletes, and professional football players. [65][66][67] Because these populations share the same risk which distinguished them from other populations, that is, they have increased chance of motor nerve injury, we reasoned that motor nerve injury might trigger the development and/or accelerate the progression of ALS. Therefore, we conducted a study to determine the immune responses after nerve injury in mouse ALS model.…”
Section: Th17 Cells Nerve Injury and Alsmentioning
confidence: 99%
“…PON2 and PON3 share this function (Draganov et al, 2000;Ng et al, 2001). A higher incidence of ALS among Gulf war veterans and farmers suggested that chemical exposure may be a risk factor for ALS (Chió et al, 1991;Horner et al, 2003). Because PON proteins reduce oxidation and are able to detoxify neurotoxins these proteins have been investigated for association with ALS.…”
Section: Paraoxonase Genes (Pon)mentioning
confidence: 99%
“…Environmental exposures during the Gulf war have been proposed as the explanation for an increased incidence of ALS among Gulf War veterans (Haley 2003, Horner et al, 2003.…”
Section: Aetiology Pathology and Pathogenesis Of Motor Neuron Diseasementioning
confidence: 99%